Trends and Patterns of Growth, Development, Achievements of China and India: A Comparative Analysis - Biswa Nath Bhattacharyay; Madhurima Bhattacharyay (Center for Economic Studies and ifo Institute (CESifo), 2016)
Even before the onset of the 2008 global financial crisis and ongoing European debt crisis, much attention has been given to the re-emergence of the Asian giants, the People's Republic of China (PRC) and India. Both countries have attained unprecedented growth and economic development—PRC and India became the second and fourth largest economies of the world, respectively. Moreover, these countries remarkably improved their per capita income as PRC increased its per capita GDP by 13-fold from US341 in 1990 to US4,421 in 2010 whereas India posted a four times growth from US384 in 1990 to US1,342 in 2010. This has resulted in a remarkable poverty reduction in the last two to three decades in the two economies. PRC and India share several common characteristics, prospects and challenges. However, their approaches to growth and development as well as growth models have been different. The major objective of this paper is to compare the policies, institutions, strategies, reforms and market conditions that contributed to the rapid growth and development of the PRC and India which can provide lessons to the developing world, particularly emerging economies, that are also struggling to improve their economic development and quality of life amidst economic growth. This paper attempts to examine the differences between PRC and India in terms of trends and patterns of growth and development, economic models, sources and drivers of growth; achievements, policies and institutions since last three decades.
Keywords: O10; O11; O12; O20; O21; O24; O40; O43; O57; 330; growth and development; People Republic of China; India; comparative analysis; economic reforms; models; policies and institutions; emerging economies